2005
DOI: 10.1590/s1413-86702005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus RNA in saliva samples from patients with seric anti-HCV antibodies

Abstract: We examined the frequency of HCV-RNA in saliva samples from anti-HCV positive patients. Both plasma and saliva samples from 39 HCV patients (13 with normal liver enzymes, 19 with abnormal liver enzymes and 13 with cirrhosis) were investigated. Stimulated saliva and fresh plasma were centrifuged (900 x g,10 min) and stored at -70 o C, after the addition of guanidine isothiocyanate RNA extraction buffer. HCV-RNA was detected by RT-nested-PCR (amplification of HCV-cDNA for two rounds, using HCV primers 939/209 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Traditional diagnosis and monitoring of HBV and HCV infections consist mainly of blood-based and serological tests evaluating viral load as well as viral antibodies and antigens. Interestingly, reports have indicated that HBV and HCV DNAs, antibodies, and viral antigens not only exist in the saliva of infected subjects but also correlate well with blood samples (75,76,77). These findings suggest a potential role for saliva as a noninvasive mode of HBV and HCV diagnosis and disease state monitoring.…”
Section: Infectious Diseasementioning
confidence: 89%
“…Traditional diagnosis and monitoring of HBV and HCV infections consist mainly of blood-based and serological tests evaluating viral load as well as viral antibodies and antigens. Interestingly, reports have indicated that HBV and HCV DNAs, antibodies, and viral antigens not only exist in the saliva of infected subjects but also correlate well with blood samples (75,76,77). These findings suggest a potential role for saliva as a noninvasive mode of HBV and HCV diagnosis and disease state monitoring.…”
Section: Infectious Diseasementioning
confidence: 89%
“…Consequently, such epidemiologic investigations can allow researchers to assess risk of disease based on HOMIM-based targeted characterization by comparing to already databased phyla or genera. Infectious diseases, local diseases, and systemic diseases that have been identified are HIV-1, HIV-2, hepatitis A, hepatitis B, hepatitis C, malaria, dengue fever, tuberculosis, Ebola virus disease, herpes simplex, disease caused by and correlated to Epstein-Barr virus, herpesviruses infection, cytomegalovirus-caused illnesses, oral cancer, Crohn’s disease, pancreatic cancer and chronic pancreatitis, periodontal disease, dental caries, and obesity [53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72]. …”
Section: Varieties Of Biomarkers For Diagnostics In Salivamentioning
confidence: 99%
“…Salivary transcripts can also be used to detect viruses in the oral cavity. The most studied virus for diagnosis associated with salivary RNA is hepatitis C (Wang et al , ; Young et al , ; Chen et al , ; Kage et al , ; Rey et al , ; Goncalves et al , ). Other studied viruses include hepatitis A (Mackiewicz et al , ; Amado et al , ) and immunodeficiency virus‐1 (Kakizawa et al , ; Shugars et al , , ).…”
Section: Diagnostic Use Of Salivary Rnamentioning
confidence: 99%